The impact of training evaluation on Employee productivity: the mediation role of Job performance in public organizations in UAE - Al Ali, Rashid Ali (2022)
Today, many public organizations adopt training programs to develop the productivity and performance of employees. While most previous studies have examined the direct influence of training programs on the productivity of employees, there is a lack of empirical evidence on the indirect effect of training evaluation on employee productivity through job performance. Accordingly, the aim of this study is to examine the mediation role of job performance on the relationship between training evaluation and employee productivity in the General Directorate of Residency and Foreigners Affairs in the UAE (GDRFA). To achieve the objectives and answer research questions, this study used quantitative methods, Structural Equation Modeling methods were applied to validate the conceptual framework and hypotheses. The questionnaire a is data collection tool. The population is the workforce inside GDRFA. The data analysis was conducted on 387 valid questionnaires with a response rate 86%. The findings indicate that training has a significant effect on the employee productivity, while job performance partially mediates this relationship. Based on this outcome, the leaders in GDRFA should foster job performance by developing task and contextual performance. The adoption of training evaluation must be conducted after the competition of training programs in public organizations and based on modern approaches such as the Kirkpatrick model in order to enhance the productivity of employees.